Penguatan Kompetensi Editor dan Desk Reviewer melalui Workshop Kaidah dan Strategi Desk Evaluation untuk Meningkatkan Mutu Pengelolaan Jurnal Ilmiah - Andriyani Andriyani (Jurnal Aksi Dosen dan Mahasiswa, 2026)
The quality of scientific publications is greatly influenced by the quality of the editorial process, particularly the desk evaluation stage, which serves as an initial screening before articles enter the peer review process. In practice, many journal editors and reviewers still lack a uniform understanding of article assessment indicators according to international journal standards. This condition impacts the less than optimal manuscript selection process and the quality of published articles. This community service activity aims to improve the competence of editors and reviewers through a workshop entitled "Rules and Strategies for Editor and Desk Reviewer Desk Evaluation in the Article Review Process of International Journal Standards." The activity was carried out using a participatory workshop method consisting of material delivery, interactive discussions, case studies, desk evaluation simulations, and feedback sessions. The target audience of the activity was editors, reviewers, and managers of scientific journals. The results of the activity showed that participants gained a better understanding of the differences in editor and reviewer duties, indicators for assessing scientific articles, desk rejection strategies, and techniques for evaluating novelty, methodology, and the suitability of articles to the journal's scope. The discussion revealed that the limited number of manuscripts remains a challenge, especially in unaccredited journals and journals accredited by SINTA 5 and SINTA 6. Therefore, strengthening the capacity of editors and reviewers needs to be accompanied by strategies to increase the number and quality of manuscripts through expanding the author network, promoting calls for papers, and mentoring in writing scientific articles.